Predecessors, Scholars and Researchers in Information Sciences. Contribution to Methodology for Bibliometrics Anaysis of Scientific Paradigms - Pečarić, Đilda (Array, 2009)
Development of Information Science paradigm is researched on the corpus of most cited references retrieved from doctoral dissertations in Information Science (from 1978 to 2007). New approach for analysis of scientific paradigm by empirical display of dominant zones within scientific paradigm is proposed: empirical knowledge zone, conceptual knowledge zone and research front zone. Alterations of scientific paradigm are followed across three time periods by display of most cited authors in librarianship, information systems, communicology, archivistics and documentation, museology and information science. Besides the data about most cited authors, the data about most cited references according to periods and disciplines are shown. Analysis of most cited references resulted with discovery of the dominant research topics in particular periods. Based on changes in research topics it can be concluded: a) which research topics were interesting for Information Science researchers in Croatia, and b) changes within Information Science paradigm, by tracking changes of key authors which are cited during period of thirty years. Suggested methodology can serve as a model for tracking the development of scientific paradigm in other research disciplines as well.